2018
DOI: 10.1021/acs.jnatprod.7b00961
|View full text |Cite
|
Sign up to set email alerts
|

Peloruside A-Induced Cell Death in Hypoxia Is p53 Dependent in HCT116 Colorectal Cancer Cells

Abstract: HCT116 colorectal cancer cell sensitivity to peloruside A (PLA) in normoxia is not altered by hypoxia preconditioning of the cells. We examined whether the PLA effects were altered in hypoxia and whether the activity was dependent on p53. The cytotoxicity of PLA in wild-type HCT116 cells was largely unaffected by hypoxia; however, cells in which p53 was knocked out showed resistance. Knockout of the p21 gene had little effect on the activity of PLA in hypoxia. It was concluded that the response of cells to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Peloruside A was active against murine leukemia cells [236]. Peloruside A had no significant effect on its own on phosphorylation of tau but significantly increased the levels of acetyl tubulin in neuronal cell culture [237].…”
Section: Current Status Of Microtubule Stabilizersmentioning
confidence: 93%
“…Peloruside A was active against murine leukemia cells [236]. Peloruside A had no significant effect on its own on phosphorylation of tau but significantly increased the levels of acetyl tubulin in neuronal cell culture [237].…”
Section: Current Status Of Microtubule Stabilizersmentioning
confidence: 93%
“…Under hypoxic conditions, loss of the tumor suppressor p53 (encoded by TP53) provides cancer cells with a selective advantage, hypoxia which causes resistance to therapy and promotes metastasis in CRC. 205 , 206 Recently, Li et al reported the hypoxia inducible factor 1 alpha subunit (HIF1A) directly repressed the miRNA-34a in p53-defective CRC cells under hypoxia. 207 Conversely, p53 increases expression of miRNA-34a in CRC cells without hypoxia.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…It is well known that cells are continuously disturbed by a vast variety of exogenous and endogenous stress, including oncogenes activation, unfolded proteins, genotoxic damage, physical impact, telomere erosion, and hypoxia, which disrupts the normal homeostasis of affected cells. (El-Khatib, Geara, Haddadin, & Gali-Muhtasib, 2010;Ou & Schumacher, 2018;Řehulka et al, 2018). As a key guardian of the genome, the tumor suppressor p53 is crucial for the cellular response DNA damaging stimuli to keep the genomic integrity of cells.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%